Early identification of depressive symptoms in school‐aged children: Psychometric properties and validation of a new short version of Short Mood & Feelings Questionnaire. Issue 2 (5th November 2021) - Talja, Tiina; Rantanen, Anja; Koivisto, Anna‐Maija; Fröjd, Sari; Ikonen, Riikka; Joronen, Katja
Abstract: Background: Depressive mood is a common problem among children in Western countries. Professionals in school and other health services have an important role in identifying children at increased risk for depression. The Short Mood and Feelings Questionnaire (SMFQ) is a widely used screening tool, but its 13 items still make it quite time‐consuming to complete. There is an urgent need for a quick and easy‐to‐complete self‐report depressive mood scale for use in school health examinations. Aim: This paper aims to describe and validate a revised version of SMFQ: FsMFQ‐6 is intended as a short screening tool for the early identification of depressive symptoms in children. Methods: Nationally representative data ( n  = 95, 725) were drawn from the 2017 School Health Promotion Study. The respondents were fourth‐ and fifth‐grade pupils (aged 10–12) in Finnish primary schools. The data were analysed separately by gender. The construct validity of the scale was studied by principal component analysis and confirmatory factor analysis (CFA), convergent validity by both receiver operating characteristic (ROC) analysis and Spearman's correlation coefficient. Reliability was tested by Cronbach's alpha coefficient. Results: Principal component analysis yielded a one‐component model: the Finnish Short Mood and Feelings Questionnaire 6 (FsMFQ‐6). CFA confirmed the validity of FsMFQ‐6. Compared with mood at home (AUC = 0.80) and mood at school (AUC = 0.85), overall sensitivity and specificity were optimal at cut‐off point 0. Cronbach's alpha coefficient was 0.73, indicating good internal consistency. The results for girls and boys were almost identical. Conclusion: The results confirmed the validity and reliability of FsMFQ‐6. FsMFQ‐6 recognises depressive mood in children and is suitable for screening depressive symptoms in fourth‐ and fifth‐grade pupils in Finland. However, it is important to pay close attention to children who choose the 'Sometimes' response option more than once, for that can be a sign of depressive symptoms.